The Impact of the Money Supply, Exchange Rate and Fuel Prices on the Inflation Rate - Ida Ayu Sintha Agustina; I Komang Oka Permadi (Universitas Batanghari Jambi, 2023)
The economic stability of a country is a criterion for long-term economic development. However, economic stability is a long-standing issue, particularly in developing countries. Almost all countries, both developed and developing, are struggling with economic growth and stability. The purpose of this research is to explain and re-examine the relationship between the money supply, the rupiah exchange rate, and fuel prices and the inflation rate. In this study, secondary data was used, and data was collected using time series data from 2012 to 2021. Multiple linear regression analysis, multiple coefficients of determination (R2), partial hypothesis test (t test), and simultaneous hypothesis test (F test) were used in this study and were tested using SPSS Version 22.0. The three dependent variables, namely the money supply, the rupiah exchange rate, and the price of gasoline, are said to have a positive influence on the inflation rate, either partially or concurrently, based on the test results.